Implementation of Differentiated Learning in Arabic for Children with Special Needs - Muhammad Iqbal Fuadhi; Mohammad Syah Rizal Niqie; Almar'atul Muttaqiyah; Naufal Ulya; Hisbullah Huda (UIN Syekh Wasil Kediri, Indonesia, 2025)
This study aims to identify the implementation of differentiated learning in the context of Arabic language subjects for children with special needs at Muhammadiyah 1-2 Taman Primary School and its supporting and inhibiting factors. The subjects studied include inclusion assistant teachers, subject teachers, students with special needs. The method used is descriptive qualitative where data is collected from observation, interviews and documentation, the results show that in its application differentiated learning is carried out with several stages of mapping learning needs, implementing differentiation of content, process and product in learning. several supporting factors such as active collaboration between the principal and parents in providing support, high enthusiasm and interest of students, comfortable and happy learning situations inhibiting factors in the application of differentiated learning in Arabic language subjects for children with special needs include limited ability to read and write Arabic and minimal learning motivation, unstable emotions, difficulty in concentration, limited teacher understanding in conducting initial assessments of the abilities and learning readiness of students with special needs. Penelitian ini bertujuan untuk mengidentifikasi implementasi pembelajaran diferensiasi dalam konteks mata pelajaran Bahasa Arab untuk anak berkebutuhan khusus di SD Muhammadiyah 1-2 Taman serta faktor pendukung dan penghambatnya. Subjek penelitian meliputi guru pembantu inklusi, guru mata pelajaran, dan siswa berkebutuhan khusus. Metode yang digunakan adalah deskriptif kualitatif di mana data dikumpulkan dari observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa dalam penerapannya, pembelajaran diferensiasi dilakukan dengan beberapa tahapan pemetaan kebutuhan belajar, implementasi diferensiasi isi, proses, dan produk dalam pembelajaran. Beberapa faktor pendukung seperti kolaborasi aktif antara kepala sekolah dan orang tua dalam memberikan dukungan, antusiasme dan minat siswa yang tinggi, situasi belajar yang nyaman dan menyenangkan. Faktor penghambat dalam penerapan pembelajaran diferensiasi pada mata pelajaran Bahasa Arab untuk anak berkebutuhan khusus meliputi kemampuan membaca dan menulis Bahasa Arab yang terbatas dan motivasi belajar yang minimal, emosi yang tidak stabil, kesulitan berkonsentrasi, pemahaman guru yang terbatas dalam melakukan penilaian awal kemampuan dan kesiapan belajar siswa berkebutuhan khusus.